ANALYSIS OF SCIENCE ONTOLOGY CONSTRUCTION TO MUHAMMAD IQBAL'S PERSPECTIVE ISLAM - Zamroni, Zamroni; Fajri, Muhamad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Ontology examines various principal things, Muhammad Iqbal is one of the developers of ontology, so this research aims to track ontology indicators according to Muhammad Iqbal, then process them into basic instruments, in this way, researchers who have a philosophical interest in aspects of ontology have a reference for development instruments according to the ontology research context. Library research with a philosophical approach, and content analysis of library sources, are methods that are relied upon to achieve the objectives of this research. This research shows that there are 5 main indicators of the ontology of Islamic science, namely monotheism, knowledge, nature, humans, and the afterlife. Then, each of these indicators can be combined into questions according to the research context. In Islamic science, these are paradigm, orientation, and draft.